Lexical and commentary analysis of the words related to “Maad” in the Qur'an - kavous roohi; ص م (پژوهش نامه معارف قرآنی, 2020)
In the field of “Maad”, there are many words (28 words) that only 17 cases are used in this field. This article, has examined meaning of these words and common points and Conceptual differences between them from valid Arabic dictionary and commentators' views And concluded that Each of these words in this area have share semantic with other words And because of that put in the Qur'anic likes (nazayer) While not found in the Vojoh and Nazayer book. and so some words have special meaning that cant replace them with their likes (nazayer) due to the vers conception is attachment of most of this words to meccan chapters that is associated with the concept of madani chapters.نتیجه مهم دیگر تعلق غالب واژگان حوزۀ معاد به سور مکی است که مرتبط با محتوای سور مکی می باشد. نتیجه مهم دیگر تعلق غالب واژگان حوزۀ معاد به سور مکی است که مرتبط با محتوای سور مکی می باشد.